Coaching practices to develop underwater fly kick performance in swimming training - Thompson, I. M.; Warner, M.; Hudson, D.; Banks, J.; Logan, O. (International Journal of Sports Science and Coaching, 2022)
This study assessed current swimming coaching practices surrounding underwater fly kick. Ten elite coaches completed face-to-face interviews, and 56 coaches completed an online survey. Coaches use a range of methods both in and out of the pool to develop key aspects of fly kick. Sixty eight percent of coaches reported they do not have access to resources that would aid with their ability to develop fly kick. Results show that coaches are considering a range of variables when attempting to improve fly kick, with the three most important highlighted as kick frequency, kick symmetry and coordination. Coordination is reported as the variable presenting the greatest difficulties when coaching due to athlete's physical restrictions and individual differences, as well as difficulties in coaching proprioception. Coaches are using a variety of resources to inform their approaches in underwater fly kick, but report coach certification and education resources as having the lowest influence on their coaching methods. Generally, results indicate a lack of skill acquisition knowledge and education in underwater fly kick. Reflecting upon coaches` views and approaches allows for further research to develop understanding of interventions used to improve fly kick, and aids with the transfer of key research findings into practice.